Evaluation of the impact on audiences of Inside Out of Mind, research-based theatre for dementia carers - Schneider, Justine M. (Taylor and Francis, 2017)
Background Inside Out of Mind is an ethno-drama about dementia carers in hospital, intended to raise awareness of this role, and about dementia care in general. Following a successful premiere in 2013, it was taken on a live tour funded by the Big Lottery through Arts Council England to six cities. This paper explores the impact on audiences consisting largely of professional carers. Methods Mixed methods were applied; semi-structured self-completion questionnaires for post-show feedback, and one month later telephone interviews to a stratified sample of respondents. Framework analysis was used to explore the data, paying particular attention to critical comments. Results Of the 5,426 people who attended, 19% completed post-show questionnaires. Sixty-four were subsequently interviewed in depth. Both lay and professional audience members expressed heightened awareness of the needs of people with dementia. They expressed greater appreciation of the care process and the challenges faced by the people employed to care for people with dementia in hospitals and other long-term settings. Conclusions As research-based theatre this production of Inside Out of Mind afforded an effective medium for knowledge transfer. It engaged audiences with the key issues - including dignity, identity and loss - and enabled them to relate these to their own lives, while encouraging appropriate practical responses.